STRENGTHENING THE RURAL ECONOMY THRU MSME EMPOWERMENT AND FINANCIAL LITERACY FOR CHILDREN IN PALUH SIBAJI VILLAGE, PANTAI LABU DISTRICT - Muhammad Rishan Sahlaya; Faridah; Vicky Aria; Fitrah Khairuna Ulfa Lubis; Lili Raflika (Yayasan Amanah Nur Aman, 2025)
This research aims to analyze the strengthening of the village economy thru the empowerment of Micro, Small, and Medium Enterprises (MSMEs) and the improvement of children's financial literacy in Paluh Sibaji Village, Pantai Labu District. MSMEs play an important role in increasing the economic independence of rural communities, while financial literacy for children is seen as strategic for building a generation that is aware of financial management from an early age. The research method uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research results show that empowering MSMEs in Paluh Sibaji Village has contributed to increasing family income and expanding employment opportunities. On the other hand, children's financial literacy programs have a positive impact on children's mindset regarding the importance of saving, small entrepreneurship, and managing their pocket money wisely. Collaboration between MSMEs and children's financial literacy education has proven to be an effective strategy in creating sustainable economic resilience in villages. This research confirms that strengthening the rural economy lies not only in the productive aspects of the community, but also in the formation of the financial character of the younger generation.